Neuronal processes contain the essential components for the late steps of ribosome biogenesis - Claudia M. Fusco; Anja Staab; Ashley M. Bourke; Georgi Tushev; Kristina Desch; Erico Moreto Lins; Elena Ciirdaeva; Susanne tom Dieck; Nina Kaltenschnee; Alexander Heckel; Julian D. Langer; Erin M. Schuman (Proceedings of the National Academy of Sciences, 2025)
Neurons rely on spatial and temporal control of protein synthesis to respond rapidly and locally to external stimuli, a process facilitated by the dynamic localization and modification of ribosomes. While previous research has shown that neuronal activity can regulate ribosome localization and modify translation rates, little is known about ribosomal assembly within neuronal processes. Here, we investigated the potential for local ribosome maturation in rat neurons using proteomics, RNA sequencing, and imaging methods. We detected an abundance of ribosome biogenesis factors in distal neuronal compartments, particularly those associated with the late stages of ribosome assembly. Moreover, we detected cytosolic pre-ribosomal RNA species in dendrites, as well as the enzymes necessary for their processing, suggesting that local ribosome maturation can occur far from the nucleus. These findings challenge conventional models that confine ribosome biogenesis to nuclear and perinuclear regions and suggest that neurons may fine-tune local protein synthesis by regulating ribosome assembly near synaptic sites. This mechanism may enable rapid modulation of the translational capacity in response to physiological changes, regulating synaptic plasticity and local protein synthesis in neurons.